Systematic Literature Review: Penalaran Adaptif Siswa dalam Pembelajaran Matematika - Hartati, Tuti; Muhtar Gozali, Sumanang (Jurnal Gantang, 2025)
This study aims to examine trends in research methods used in articles related to students' adaptive reasoning abilities in mathematics learning from 2015 to 2024 and to describe the improvement of students' adaptive reasoning abilities. The method employed was a Systematic Literature Review (SLR) involving the identification, selection, evaluation, and data analysis of relevant articles. The reviewed articles were selected based on their relevance to students' adaptive reasoning, were published between 2015 and 2024, were sourced from Google Scholar, focused on junior high to senior/vocational high school levels, and were indexed in Sinta 1 to 3. Irrelevant articles published before 2015, not obtained from Google Scholar, outside the specified education levels, or published in proceedings and journals below Sinta 3 were excluded. Students' abilities increase by up to 82.7% with the use of Collaborative problem-solving-based tools and are very effective in improving students' adaptive reasoning abilities. This study emphasizes the importance of implementing innovative and adaptive teaching methods while considering individual student factors to enhance adaptive reasoning abilities in mathematics learning. These findings are expected to serve as a reference for educators in designing more effective teaching strategies.